A New Ceratostylis (Orchidaceae) Species From Bukidnon, Philippines - de Leon, Miguel David; Naive, Mark Arcebal; Cootes, Jim (Phytotaxa, 2017)
A new Ceratostylis species from the Kalatungan Mountain Range, one of the mountains of Bukidnon that needs further exploration, is described and illustrated. Morphological diagnostic characters of related species of the genus are discussed. Though similar to C. elmeri, the new species is clearly distinguished by the size of the flower and by its uniquely small size labellum. It is also similar to C. philippinensis, however, it can be recognized by having a marked difference in the shape of the lip, sepals, and petals.